Kondisi plankton pada tambak ikan kerapu di Desa Mesjid Lama Kecamatan Talawi Kabupaten Batu Bara, Sumtera Utara - Rumondang Rumondang; Epa Paujiah (Depik, 2020)
Abstract. Fishpond is one of the habitats from organisme such as plankton which is have a role as main food resources for organisms with high trophic level (such as fish). This objectives of the study were to determine the condition of plankton in grouper fishponds in Mesjid Lama Village, Talawi District, Batu Bara District. Plankton sampling and water quality measurements were carried out from February to June 2019. The abundance of phytoplankton in grouper fish ponds varied between 1,765-4,113 ind/L. The composition of phytoplankton species found during observation was dominated by diatom groups or Bacillariophyceae classes. The abundance of zooplankton in grouper ponds varied from 330-1,165 ind/L with the lowest abundance found at station 6 with a total of 330 ind/L and the highest abundance was found at station 4 with a number of 1,165 ind/L. The zooplankton genus that is often found is Acartia. Diversity value H '